An assessment of the role played by law enforcement agencies in the protection of children’s rights, a case study of Bulawayo Metropolitan, 2014 to 2015. - Mhora, Tawanda (Midlands State University, 2017)
The focus of this research was to explore the role of law enforcement agencies towards the protection of children’s rights in Bulawayo Metropolitan, from 2014-15. This research was inspired by the high rate of child abuse cases recorded in the province, hence the need to understand the trend, as local media would report a case of child abuse with each edition. The descriptive research design used on the qualitative data obtained from the law enforcement agencies, so as to obtain a deeper understanding of the role played by law enforcement towards child protection. An explanatory design was also employed in order to elaborate further the phenomenon of child abuse and all the forms of abuse suffered by the victims. Therefore this study makes use of 4 participants, with two participants from the law enforcement agencies and the other two from the child protection committees aimed at protecting children. The researcher subscribed into the research by the use of interviews with the participants on the efficiency of the law enforcement towards the protection of the rights of the children in Bulawayo Metropolitan. This study shows the vulnerability of children in society and shows the various forms of abuse that children are mainly prone to. Therefore the researcher clearly shows the line of thinking and suggestions of the key respondents towards understanding the role played by the law enforcement agencies towards the protection of the rights of children.